Enhancing Students' Writing Ability Using Clustering Methodology - Cucu Mida Sari; Hajjah Zulianti; Tommy Hastomo (Aksara: Jurnal Bahasa dan Sastra, 2023)
This research aims to improve students’ writing skills at SMP Negeri 15 Bandar Lampung by using the Clustering technique. The participants of this research were the students in eighth grade. The total numbers of students were 33 students. Employing classroom action research, this study was carried out for two cycles at VIIIA. The main emphasis of this study was the improvement of students' learning activities and writing skills. In cycle 1, students were less engaged, less self-assured, and the classroom environment was still out of control. The cycle one learning activities' mean score for students was 6.53, which had a subpar predicate. Cycle 2 revealed an improvement in the students. They were more engaged and self-assured, and the environment in the classroom was entertaining and under control. The students' cycle two learning activities had an average score of 7.50 and a favourable predicate. Additionally, in cycle one writing test had a mean score of 64.81, with 16 students or 48.48% passing the goal. It indicates that students' writing abilities have improved. The writing test for students in cycle 2 had a mean score of 77.39; 27 students, or 81.82%, passed the target. From the data shown, it could be concluded that classroom action research using the Clustering technique can improve students' learning activities and writing skills.